비만과 우울에 대한 사상체질별 체력 매개모형 평가 - 유성은(Sung Eun You); 고유선(You Sun Ko) (한국체육측정평가학회지, 2014)
최근 비만이 우울에 영향을 미친다는 연구들이 보고되고 있다. 본 연구는 비만이 우울에 미치는 경로에서 체력의 매개효과를 사상체질별로 살펴보고, 비만, 체력 및 우울 경로모형에 대한 평가를 검증하고자 하였다. 연구대상은 본 연구에 참여하고자 의사를 밝힌 일반 여대생 305명으로, 사상체질 및 우울 설문조사를 실시하였고 체력요인으로 근지구력, 순발력, 유연성과 비만요인으로 체지방률과 BMI를 측정하였다. 자료분석은 PASW 20.0과 AMOS 20.0을 활용하여 기술통계와 경로모형 분석(Path analysis)을 실시하였다. 그 결과는 다음과 같다. 전체대상 및 사상체질별로 연구모형과 수정모형을 비교한 결과, 전체대상과 태음인은 유의하지 않은 경로를 제약한 수정모형이 적합하였다. 그러나 소음인은 Full-path 모형인 연구모형이 적합하였고, 소양인은 연구모형, 수정모형 모두 적합도 기준에 부합되지 않았다. 또한 전체대상 및 사상체질별로 비만과 우울을 감소시키는 체력의 매개요인이 다르게 나타났다. 전체대상의 경우 순발력과 유연성은 BMI→우울 경로를 부분매개 하였으며, 체지방률→우울 경로를 완전매개 하였다. 즉 순발력과 유연성 향상이 우울을 감소시키는 효과를 보였다. 소음인의 경우 순발력이 BMI→우울 경로를 부분매개 하는 것으로 나타나, BMI가 증가될수록 우울이 높아지며, 순발력이 향상될수록 우울이 감소되는 효과를 보였다. 태음인의 경우 유연성이 체지방률→우울 경로를 완전매개 하는 것으로 나타났다. 즉 비만과 우울에 대한 체력의 매개모형 평가 검증을 통하여 태음인은 체지방률을 낮추고 유연성을 향상시킴으로써 우울 감소 효과를 기대할 수 있었다. 추후 비만, 우울 감소 및 예방을 위한 사상체질별 체력프로그램 개발과 적용이 이루어져야 할 것이다. Recent researches are reporting the influence of obesity on depression. This study aims to examine mediation effect of physical fitness on how obesity affects depression depending on sasang constitution, and to verify the evaluation on path model of obesity, physical fitness, and depression. The subjects of study are 305 female college students who agreed to participate in this study; survey on their sasang constitutions and depression, and measurement of muscular endurance, power, and flexibility as physical fitness factors and body fat percentage and BMI as obesity factors were implemented. Data was analyzed by Path analysis and descriptive statistics using PASW 20.0 and AMOS 20.0. The results were as follows. As the result of comparing research model of sasang constitution and whole research subjects with correction model, correction model with limited insignificant path was suitable for whole research subjects and Tai-eum persons. For So-eum persons, however, research model, which is full-path model, was suitable. So-yang persons were not coincided for goodness of fir for either research model or correction model. In addition, mediation factor of physical fitness that reduces obesity and depression was different for whole research subjects and sasang constitutions. In case of whole research subjects, power and flexibility partially mediated the path from BMI to depression, while they fully mediated the path from body fat percentage to depression. That is, improvement in power and flexibility was effective in decrease of depression. In case of So-eum persons, power partially mediated the path from BMI to depression; depression increased as BMI increased, while it decreased as power improved. For Tai-eum persons, flexibility fully mediated the path from body fat percentage to depression. Thus, according to the evaluation and verification on mediation model of physical fitness in relation with obesity and depression, depression of Tai-em persons is expected to reduce by lowering body fat percentage and improving flexibility. For future, development and application of physical fitness programs depending on sasang constitution for reduction and prevention of obesity and depression seem necessary. KCI Citation Count: 3